La La traducción de la ironía: Memórias póstumas de Brás Cubas de Machado de Assis - Díaz Ferrero, Ana María; de Almeida Sandes, Egisvanda Isys (Revista de Letras, 2024)
Abstract The translation of irony is a complex task, not only because to transmit it with quality the translator needs the necessary skills to understand it in its entirety, but also because subjective aspects are involved in its production, linguistic, socio-cultural and specifically translation. The skills which will enable the translator to successfully complete both the comprehension phase of the original text and the expression phase in the target language are the humorous competence of Raskin (1985) and the principle of cooperation of Grice (1975). In addition, translation competence is obviously a fundamental component since, according to the techniques used, irony can be correctly transferred to the target language, partly altered or transmitted in an erroneous way. This article analyses the elements necessary for creating and understanding irony and, in particular, the on the other hand, some examples of translation from Portuguese to Spanish of certain ironic passages taken from the novel The Posthumous Memoirs of Brás Cubas by the Brazilian writer Machado de Assis are commented.